Embracing sustainability: harnessing a fiction in dealing with dominant firms? - Mariateresa Maggiolino (Market and Competition Law Review)
This article explores the intersection of competition law and sustainability, particularly focusing on the role that Article 102 of the Treaty on the Functioning of the European Union may play in this context. It presents a novel approach, categorizing the relationship between Article 102 and sustainability into four scenarios, and examining the corresponding actions antitrust authorities should take. It identifies key challenges when competition protection conflicts with sustainability, analysing the pros and cons of two potential approaches: a bottom-up method, based on consumer willingness to pay for sustainability, and a top-down approach that integrates sustainability into antitrust goals. Finally, the paper delves into the arguments against penalizing dominant firms for actions that harm sustainability without infringing upon competition.